The rise and fall of primary producers and consumers in a multiply-stressed shallow lake (Lake Qilu, China) over the last 200 years - Anna-Marie Klamt (Elsevier, 2021)
In this multi-proxy palaeo study, the response of primary producers and consumers to anthropogenic disturbances in a large shallow lake was investigated. Overall, eutrophication and water-level changes (partly inferred by bisaccate pollen grains) are well-reflected in changes in sedimentation rates of pigments, diatom and cladoceran species composition and other proxies (e.g. Rhabdocoela oocytes). In particular, the stepwise decrease in relative abundance of Pediastrum simplex compared to P. boryanum/P. duplex proved to be a good indicator for eutrophication intensity. Furthermore, reductions in the body size (i.e. coenobia diameter) of Pediastrum simplex were clearly related to phases of low visibility that were caused by lake damming in the 1950 s and by accelerating eutrophication in the 1990 s. During the latter period, strong algal growth led to turbid conditions, which are indicated by the co-occurrence of the diatoms Fragilaria crotonensis, Aulacoseira ambigua and A. granulata, the green algae Staurastrum sp. as well as the cladoceran Anthalona cf. milleri. This study highlights that subfossil remains, which are often found in, for instance, standard cladoceran analysis (green algae such as Pediastrum spp. and Staurastrum spp. or bisaccate pollen grains), can add valuable information to the reconstruction of past environmental conditions and biotic response. Such better and more holistic understanding of freshwater ecosystems is crucial to meet future challenges in a rapidly changing world.